Biomechanics of stabbing knife attack for trauma surgeons in Korea: a narrative review - Kun Hwang; Chan Yong Park (Journal of Trauma and Injury)
The aim of this paper was to review the biomechanics of knife injuries, including those that occur during stabbing rampages. In knife stab attacks, axial force and energy were found to be 1,885 N and 69 J, respectively. The mean velocity of a stabbing motion has been reported to range from 5 to 10 m/sec, with knife motions occurring between 0.62 and 1.07 seconds. This speed appears to surpass the defensive capabilities of unarmed, ordinarily trained law enforcement officers. Therefore, it is advisable to maintain a minimum distance of more than an arm's length from an individual visibly armed with a knife. In training for knife defense, particularly in preparation for close-quarter knife attacks, this timing should be kept in mind. Self-inflicted stab wounds exhibited a higher proportion of wounds to the neck and abdomen than assault wounds. Injuries from assault wounds presented a higher Injury Severity Score, but more procedures were performed on self-inflicted stab wounds. Wound characteristics are not different between nonsuicidal self-injury and suicidal self-wrist cutting injuries. Consequently, trauma surgeons cannot determine a patient's suicidal intent based solely on the characteristics of the wound. In Korea, percent of usage of lethal weapon is increasing. In violence as well as murders, the most frequently used weapon is knife. In the crimes using knife, 4.8% of victims are killed. Therefore, the provision of prehospital care by an emergency medical technician is crucial.